Paciente masculino de 65 años de edad con Diabetes Mellitus Tipo II y Dislipidemia. - Esteves Flores, Fidel Estefano (2020)
The present case study is about a 65-year-old elderly person, has 3 children and currently resides in the City of Babahoyo, Los Ríos Province, with a history of Type II Diabetes Mellitus for 8 years. He complies with his pharmacological treatment but nevertheless, his diet is inadequate and added to this lack of activity. Among the paternal family pathological antecedents is Type II Diabetes Mellitus, Hypertension and Cancer. In recent weeks she has had a severe headache and periods of maintenance insomnia, as well as fatigue and work stress. The Nutritional Status Assessment reflects a Body Mass Index of 21.17 kg / m², resulting in low weight. Biochemical tests reflect hyperglycemia and dyslipidemia. We opt for a nutritional treatment focused on controlling blood glucose and lipid profile. For which a nutritional plan is carried out, taking into account the socioeconomic situation and pathological condition of the patient. The type of diet that will be prescribed will be hypohydrocarbon, divided into 5 meals a day, which is characterized by the control of carbohydrates, in addition to the intake of fruits, vegetables and fiber that will help to stabilize blood glucose and lipid levels. Along with this, the follow-up that had a period of two months, where favorable results were observed in the patient's health condition.